DNA on drugs. (December 2022) - Griffin, Amy; Kirkbride, Paul; Henry, Julianne; Painter, Ben; Linacre, Adrian
Abstract: The use of illicit drugs is a continuing blight on society. Detecting DNA from individuals involved in the manufacturing and distribution of drugs can provide valuable investigative information or strategic intelligence which, in turn, can be used to disrupt the supply and distribution of illicit drugs. Our study details the transfer, persistence, prevalence, and recovery of human DNA on the exterior of tablets and capsules, as well as within drug powders. Various experiments were conducted to mimic stages in the creation and packaging of tablets and capsules. We showed that the act of brief contact (1–3 s) is sufficient to generate informative DNA profiles that can be uploaded and compared to databases internationally. This work complements chemical drug profiling data by linking seizures to each other and individuals via DNA profiles, providing information to prosecution or intelligence agencies. The generation of DNA information from illicit drug preparations is another tool that can be used in the fight against illicit drug manufacture and distribution.